Apparent Source-Level Efficiency of Internal Electric and External LPG Heating in a Laboratory Vacuum Evaporator - Erwin Erwin; Maulana Alfa Rizki; Syarif Abdullah; Slamet Wiyono (Politeknik Manufaktur Negeri Bangka Belitung, 2026)
Background: Vacuum evaporation lowers boiling temperature, but performance depends on heat-source power and location, vacuum level, auxiliary demand, and the analytical boundary. This study compared an internally coupled electric resistance heater with an external LPG burner in the same laboratory vacuum evaporator using one non-replicated Water Boiling Test per configuration and 40 kg of water. Temperature, gauge pressure, water mass, reservoir temperature, and electrical variables were recorded every minute. The electric run lasted 367 min at 0.548 kW average source power; the LPG run lasted 300 min, consumed 0.80 kg fuel, and averaged 2.049 kW. LPG reached 65 °C at 35 min and evaporated 7.8 kg (0.0260 kg/min), whereas the electric heater reached 55 °C near the end and evaporated 2.4 kg (0.00654 kg/min). Apparent source-level efficiencies from a common sensible-plus-latent balance were 78.2% for electricity and 62.7% for LPG. A ±1 °C sensitivity changed these estimates by about ±1.39 and ±0.45 percentage points, respectively. Including vacuum-pump electricity reversed the system-level ordering. Because power, pressure, duration, and endpoints were not matched, the results describe two operating states rather than a causal heater-location effect.